Bile duct regeneration and immune response by passenger lymphocytes signals biliary recovery versus complications after liver transplantation. Issue 11 (26th October 2017) - Junger, Henrik H.; Schlitt, Hans J.; Geissler, Edward K.; Fichtner‐Feigl, Stefan; Brunner, Stefan M.
Abstract : This study aimed to elucidate the impact of epithelial regenerative responses and immune cell infiltration on biliary complications after liver transplantation. Bile duct (BD) damage after cold storage was quantified by a BD damage score and correlated with patient outcome in 41 patients. Bacterial infiltration was determined by fluorescence in situ hybridization (FISH). BD samples were analyzed by immunohistochemistry for E‐cadherin, cytokeratin, CD56, CD14, CD4, CD8, and double‐immunofluorescence for cytokine production and by messenger RNA (mRNA) microarray. Increased mRNA levels of adherens junctions ( P < 0.01) were detected in damaged BDs from patients without complications compared with damaged BDs from patients with biliary complications. Immunohistochemistry showed increased expression of E‐cadherin and cytokeratin in BDs without biliary complications ( P = 0.03; P = 0.047). FISH analysis demonstrated translocation of bacteria in BDs. However, mRNA analysis suggested an enhanced immune response in BDs without biliary complications ( P < 0.01). Regarding immune cell infiltration, CD4 + and CD8 + cells were significantly increased in patients without complications compared with those with complications ( P = 0.02; P = 0.01). In conclusion, following BD damage during cold storage, we hypothesize that the functional regenerative capacity of biliary epithelium and enhanced local adaptive immune cell infiltration are crucial for BD recovery. Such molecular immunological BD analyses therefore could help to predict biliary complications in cases of "major" epithelial damage after cold storage. Liver Transplantation 23 1422–1432 2017 AASLD.